Tree Tales: Arborealities, Memory and Conflict in Elif Shafak’s The Island of Missing Trees - Angeline Nikita D,; Dr. P. Mary Vidya Porselvi, (International Journal of Scientific Research in Science and Technology, 2024)
When conflicts overtake and divide a society, the events are recorded in history texts and made known to the world. Oftentimes, the story of the victor’s side dominates the narrative and much has been said over the centuries about the need to bring to the forefront the story of the suppressed. But nowhere in these arguments was the need to record the effects of these destructions on the natural world ever been an area of concern, because it is always assumed that the natural world merely becomes the passive background for agential human actions. What many fail to realise is the fact that trees are silent spectators to the happenings around them, both the good and the bad, and they therefore become invaluable sources for understanding our history. Arboreal beings have been there long before we came and will continue to exist long after our time, and they carry all that they witness and experience in their very being; trees therefore are memory keepers of days bygone and storytellers of time who have not been given their due attention and respect. Elif Shafak’s The Island of Missing Trees is a representation of a literary text that brings forth this hitherto unexplored materiality of our arboreal companions. Drawing heavily from material ecocriticism and its concept of ‘storied matter’, this paper aims to explore the creative and narrative agency of arboreal beings through the character of the fig tree who acts as the narrator in the novel.
Keywords: Ecocriticism; Storied Matter; Arboreality; Storytelling; Memory; Conflict